Modern contraceptive use among women living with HIV/AIDS at the Korle Bu Teaching Hospital in Ghana. Issue 1 (31st January 2018) - Samba, Ali; Mumuni, Kareem; Adu, Joseph A.; Sefogah, Promise E.; Kudzi, William; Nartey, Edmund T.
Abstract: Objective: To examine factors influencing contraceptive use among women living with HIV/AIDS. Methods: The present cross‐sectional study included a randomly selected sample of sexually active females aged 15–60 years who were living with HIV/AIDS and receiving care at the HIV Clinic, Korle Bu Teaching Hospital, Accra, Ghana, between September 1 and November 31, 2016. Data were collected via a structured interviewer‐administered questionnaire. Results: Among 202 women who completed the survey, 50 (24.7%) were using contraceptives. Of the women using contraception, 39 (78%) were married and 6 (12%) were cohabiting. Twenty‐eight (56%) reported that their primary sexual partners were HIV‐positive, 14 (28%) had HIV‐negative partners, and 8 (16%) did not know their partner's HIV status. Condoms were used by 42 (84%) women and the majority (41 [82%]) wanted to have more children; almost all (47 [94%]) had received counseling on contraceptive use. Overall, 133 (65.8%) and 45 (22.3%) women reported that they would prefer to share their family planning concerns with a doctor and nurse, respectively, at the HIV clinic. Conclusion: Women living with HIV/AIDS desired more children but preferred to share their family planning concerns with their clinician at the HIV clinic. Integrating HIV care and reproductive health services could help these women achieve childbearing goals safely. Abstract : A majority of participants with HIV/AIDS wanted to have children. Integrating HIV/AIDS care with reproductive health services could help these women achieve childbearing goals safely.